Finite element analysis on the effect of jointed dryboard and overlapped profiled steel sheet in PSSDB wall with openings / Norashyura Ibrahim (Faculty of Civil Engineering, 2003)
This report presents the analysis of double skinned composite wall panel as load bearing wall using Profiled Steel Sheet Dry Board (PSSDB) with door opening effect of jointed dryboard and overlapped Profiled Steel Sheet in PSSDB walling unit. The composite panel system consists of profiled steel sheeting (Bondek II) as core component connected to cement bonded rubber wood particleboard (cemboard) using simple mechanical connectors. The performance pf PSSDB to resist the uniaxial compressive load as a load bearing structure will be analysed. The failure criteria of the panel according to displacement, stress and strain contours and the deformed shape plots of the PSSDB panel with door and window opening will be determined using the finite element analysis (FEA) known as LUSAS. The modelled analysis will be compared with the experimental findings done by Zuhairi (2003) and Rashid (2003)